Electromagnetic transient modelling and simulation of power converters based on a piecewise generalised state–space averaging method. Issue 16 (12th December 2018) - Wang, Lei; Deng, Xinchang; Hou, Junxian; Wang, Tiezhu
Abstract : Common averaging methods are studied for modelling a grid‐connected converter in renewable energy domain to balance accuracy and efficiency of electromagnetic transient simulation. A piecewise generalised state–space averaging (P‐GSSA) method is proposed for converters with large‐scale renewable energy connected to the grid. The piecewise technique is applied to the GSSA model of converters, which combine time segment with similar operating characteristics. In addition, multi‐time scale modelling is successfully achieved for the grid‐connected converters in the renewable energy domain. An example is simulated according to the P‐GSSA model proposed in this paper, and simulation results show that the proposed model can provide an efficient simulation of power converters connected to the grid in the domain of large‐scale renewable energy.